FACTORS INFLUENCING THE ADOPTION OF CLIMATE SMART AGRICULTURAL PRACTICES IN SELECTED COUNTRIES OF AFRICA: A REVIEW - Goni, I. C.; Garba, M.; Bose, A.A.; Abdullahi, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The review assessed factors influencing the adoption of Climate Smart Agricultural (CSA) practices in Ethiopia, Ghana and Nigeria. The Socio-economic characteristics of the farmers revealed that majority (85.46%, 43.40% and 59.39%) were male in Ethiopia, Ghana and Nigeria respectively. The result also revealed that the mean age of the respondents were 48.6, 35.3 and 39.3years in Ethiopia, Ghana and Nigeria respectively. The educational level of the farmers in Ghana revealed that almost half (49.7%) were formally educated. The review also showed that 42% of the farmers in Nigeria had higher education while 35.22% had basic education in Ethiopia. The mean household size of the farmers in the three Countries i.e. Ethiopia Ghana and Nigeria were 8, 7 and 8years respectively. The review also showed that age, farming experience and farm size and access to credit were significant (P<0.01) in influencing the adoption of climate smart agricultural practices in Ghana and Nigeria. Similarly, age, level of education and farm size were significant (P<0.05) in influencing adoption of climate smart agricultural practices in Ethiopia, Ghana and Nigeria while sex, level of education and access to credit were significant(P<0.10) in Ghana and Nigeria respectively. The Review concluded that age, level of education, farming experience, farm size and sex were the factors influencing the adoption of climate smart agricultural practices in the review area. The Review recommended that private sectors should be involved in establishing private extension services in other to educate the farmers on the effect of climate change and the importance of CSA practices.